Design and implementation of PC to PC data transmission using wireless visible light communication system - Reyhane Jalil; Adnan Sabbar; Hassan Falah Fakhruldeen; Feryal Ibrahim Jabbar (Institute of Advanced Engineering and Science, 2022)
In this paper a laser-based visible light communication system for PC to PC data transmission has been designed, simulated, and implemented. This type of communication uses light waves in the visible spectrum (380 nm to 750 nm) to deliver data. Visible light communication is any way of transmitting data using visible light. In order to avoid being detected by human eyes, this kind of communication sends information at a slower rate than human vision. Visible light communication is significantly more reliable and capable of high information transmission rates than existing wireless technologies such as Wi-Fi, Bluetooth, and others that use radio frequency spectrum. Laser-based visible light communication systems are low-cost, low-power, and do not require radio interference studies. A diode laser is frequently used to create the signal carrier. Due to its high efficiency, it can transmit data as well as illuminate. Light waves can't be intercepted because they can't penetrate opaque objects, signifying a very secure connection.